(untitled) (Research, Society and Development, 2024)
Smoking is one of the main preventable causes of global mortality and is associated with various diseases, including cancer, cardiovascular and pulmonary diseases. The effective management of smoking cessation represents a significant challenge for health professionals, given nicotine addiction and the other diverse factors that influence smoking behavior. This literature review aims to analyze the management and cessation of smoking in primary health care, its effects and the role of professionals who serve this population. The PRISMA strategy was used to select articles from various databases, and 21 articles were selected for this study. It was observed that the combination of different therapeutic approaches, together with ongoing support, is fundamental to increasing success rates in smoking cessation. Thus, support groups and the training of health professionals to meet the demands of these patients is essential for good results and quitting.